Alpha-lipoic acid modulates the diabetes mellitus-mediated neuropathic pain via inhibition of the TRPV1 channel, apoptosis, and oxidative stress in rats - Yazğan, Betül; Yazğan, Yener; Nazıroğlu, Mustafa (Springer Science and Business Media LLC, 2023)
Diabetes mellitus (DM) is a chronic syndrome involving neuropathic pain. Increased oxidative stress in DM is assumed to increase free reactive oxygen radicals (ROS) and causes diabetic damage. The sciatic nerve (ScN) and dorsal root ganglion (DRG) both contain high levels of the TRPV1 channel, which is triggered by capsaicin and ROSs and results in increased Ca2+ entry into the neurons. Alpha-lipoic acid (ALA) is considered an important part of the antioxidant system. To better characterize the protective effects of ALA on the DM-induced neuronal through TRPV1 modulation, we investigated the role of ALA on DM-induced neuropathic pain, oxidative ScN, and DRG damage in diabetic rats. Forty adult Wistar albino female rats were divided into four groups as control, ALA (50 mg/kg for 14 days), streptozotocin (STZ and 45 mg/kg and single dose), and STZ + ALA. Rats were used for the pain tests. After obtaining the DRGs and ScN, they were used for plate reader, patch-clamp, and laser confocal microscope analyses. We observed the modulator role of ALA on the thresholds of mechanical withdrawal pain (von Frey test) and hot sensitivity pain (hot plate test) in the STZ + ALA group. The treatment of ALA decreased STZ-induced increase of TRPV1 current densities, intracellular free Ca2+ concentrations (Fura-2 and Fluo - 3/AM), ROS, caspase 3, caspase 9, mitochondrial membrane potential, and apoptosis values in the ScN and DRG neurons, although its treatment induced the increase of cell viability and body weight gain. The treatment of ALA acted a neuroprotective role on the TRPV1 channel stimulation-mediated Ca2+ influx, neuropathic pain, and neuronal damage in diabetic rats. The neuroprotective role of ALA treatment can be explained by its modulating the TRPV1 channel activity, intracellular Ca2+ increase-induced oxidative stress, and apoptosis.
Keywords: Oxidative Stress; Thioctic Acid; Ganglia, Spinal; Animals; Neuralgia; TRPV Cation Channels; Apoptosis; Rats, Wistar; Reactive Oxygen Species; Rats; Diabetes Mellitus, Experimental; 3. Good health